Opacity and effective field theory in anti-de Sitter backgrounds - Fichet, Sylvain [UNESP] (American Physical Society (APS), 2019)
We consider quantum field theory in a five-dimensional anti-de Sitter background, possibly truncated by four-dimensional (4D) branes. In the Euclidian version of this space, it is known that propagators exponentially decay when they go far enough toward the Poincaré horizon, i.e. deep enough into the IR region of the AdS bulk. In this note, we show that an analogous property exists in Lorentzian AdS. The exponential suppression is found to occur in the presence of bulk interactions dressing the AdS propagators. We calculate one-loop gravitational dressing and find that the suppression effect comes from the scalar component of the 5D graviton. We then argue that, at least at strong coupling, this exponential decay censors the region of spacetime where the 5D effective field theory would become invalid. As an application we estimate the rate for the cascade decay of bulk fields-which are known to produce soft spherical events with high multiplicity-and find this rate to be exponentially suppressed.